Application Of Public Policy In The Implementation Of An Integrated Dynamic Archiving Information System In Tegal Regency - Saepurrohman, Saepurrohman; Permana, Ipik (Jurnal Polisci, 2025)
This article discusses the implementation of public policy in the administration of the Integrated Dynamic Archival Information System (SRIKANDI) in Tegal Regency, based on Tegal Regent Regulation No. 80 of 2023 as the legal basis for implementation. The Tegal Regency Library and Archives Office serves as the primary implementing agency responsible for coordination, socialization, and management of the SRIKANDI system within the local government. This study aims to identify the factors supporting and influencing the implementation of public policy, thereby identifying obstacles and potential improvements. This study also employs a descriptive qualitative method, with data collection techniques including in-depth interviews, observations, and documentation. Analysis is conducted using Edward III's policy implementation theory, which emphasizes four key indicators: communication, resources, implementer disposition, and bureaucratic structure. The research findings indicate that the implementation of SRIKANDI is still in the strengthening and adjustment phase, particularly in terms of budgetary support, information technology infrastructure, and equitable training for all OPDs. However, the existence of the Regent's Regulation has provided legitimacy and a clear legal framework for the implementation of this system. The active involvement of the Library and Archives Department as the leading sector, along with the establishment of a Help Desk team, constitutes a strategic step in ensuring the sustainability of the implementation. This study concludes that the implementation of public policy in the implementation of SRIKANDI requires synergy between regulations, human resource capacity building, infrastructure support, and coordination among work units. With the strengthening of these dimensions, Tegal Regency has the potential to become a model region in the implementation of an effective and sustainable digital archiving system